Pengaruh konsumsi susu kedelai terhadap amenorhoe sekunder pada remaja putri periode late adolescence di Dayah Insan Qur’ani Aceh Besar - Yusnaini Yusnaini (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2020)
Secondary amenorrhea is a menstrual cycle that occurs in women who have menstruated but does not increase menstruation within 3-6 months. The key to the menstrual cycle depends on changes in estrogen levels. Soybeans are the main source of phytoestrogens which play a role in stabilizing estrogen levels in the body, whereas 250 ml of soy milk contains 40 mg of phytoestrogens. The purpose of this study was to determine how to consume soy milk against changes in secondary amenorrhea in young women. This research is a descriptive-analytic conducted cross-sectionally. This type of research is an easy experiment with a non-randomized posttest group design. The research sample is young women who change secondary amenorrhea which is grouped into 2 groups of 17 people each. Data collection was conducted from August 2 to October 19, 2016. The statistical test used was the Wilcoxon test. The results showed that normal menstruation occurs in secondary amenorrhea adolescents after being given soy milk which is equal to 82.4% while in adolescents who are given sweetened condensed milk only by 29,4%. Statistical tests show the results of p= 0,002. The conclusion, there is a change in secondary amenorrhea between the samples gave soy milk, and those given sweetened condensed milk. Suggestions, it is necessary to provide a daily menu for students so that the menstrual cycle is maintained.